ادمان النترنت و علاقته بعادات الاستذكار لدى تلاميذ السنة الأولى ثانوي - بلعسل, ايمان (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
تهدف الدراسة إلى الكشف عن علاقة إدمان الأنترنت بعادات الاستذكار لدى تلاميذ السنة أولى ثانوي بثانوية محمد بن أحمد عبد الغني بولاية مستغانم، حيث اعتمدنا على المنهج الوصفي، وشملت عينة الدراسة(67) تلميذا من بينهم(32)ذكرا و(35) أنثى للسنة الدراسية 2023 ـ2024 وتم الاعتماد على مقياس الإدمان على الأنترنت لدكتور إبراهيم الشافعي ومقياس عادات الاستذكار لمكرتار فاتن، ولتحليل النتائج اعتمدت الباحثة على معامل الارتباط بيرسون واختبار الفروق(ت)، وذلك بالاعتماد على برنامج الرزم الإحصائية للعلوم الاجتماعية SPSS 26، وبعد المعالجة والتحليل توصلت الدراسة الى النتائج التالية: ـ لا توجد علاقة دالة إحصائيا بين الإدمان على الأنترنت وعادات الاستذكار. لدى تلاميذ السنة أولى ثانوي. ـ توجد فروق دالة إحصائيا في الإدمان على الأنترنت لدى تلاميذ السنة أولى ثانوي تغزى لمتغير التخصص لصالح الأدبيين. ـ لا توجد فروق دالة إحصائيا في متوسطات عادات الاستذكار لدى تلاميذ السنة أولى ثانوي. تعزى لمتغير التخصص.
دراسة ميدانية بثانوية محمد بن احمد عبد الغني بولاية مستغانم
The study aims to Reveal the relationship of internet addiction on the study habits of first year secondary school students at Mohammed ben Ahmed Abdel Ghani secondary school ,where we relied on the descriptive approach and the study sample included 67 students , including 32 males and 35 females for the academic year 2023 /2024 the internet addiction scale was relied upon by Dr Ibrahim Al shafi’I and the study habits scale by Makrter Faten to analyze the results ,the research relied on the Pearson correlation coefficient and the t- test , relying on the statistical package for the social sciences (SPSS) program and after treatment and Analysis: the study reached the following results. _ there is no statistically significant relationship between Internet addiction and study habits among first- year secondary school students _There are statistically significant differences in Internet addiction among first secondary school students due to a varibal specialization for the benefit of writers. _There are no statistically differences in the averages of recall habits among first year secondary school students. be consold for the specialization variable.
Keywords: إدمان الأنترنت، عادات الاستذكار، تلاميذ السنة أولى ثانوي: Internet addiction, study habits, first year secondary school studen